2017
DOI: 10.5539/jms.v7n2p45
|View full text |Cite
|
Sign up to set email alerts
|

Housing, Finance, Policy and the Wider Economy

Abstract: Building an understanding of the complex dynamics between housing, finance, policy and the wider economy is a critical step towards the development of a strategy that permits policy makers to leverage resources and enable the housing market to function better in the pursuit of economic, financial and social objectives. Powerful real, legislative and financial circuits suggest that an enabling strategy for housing can support societal progress and wellbeing. By summarizing the key findings in the existing theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
(147 reference statements)
0
3
0
Order By: Relevance
“…In Asian countries, housing takes up 20-50% of the total consumption and 40-70% of average household wealth . The wealth effect interrelates housing (including its financing) with the economy, in addition to the financial accelerator (Winkler, 2017).…”
Section: Flpp's Impact On Economic Performancementioning
confidence: 99%
“…In Asian countries, housing takes up 20-50% of the total consumption and 40-70% of average household wealth . The wealth effect interrelates housing (including its financing) with the economy, in addition to the financial accelerator (Winkler, 2017).…”
Section: Flpp's Impact On Economic Performancementioning
confidence: 99%
“…The housing satisfies the need of human for shelter, it can be a major wealth component, and it is an important sector of the economy. Housing plays a critical role in labour economics and the urbanization process (Winkler, 2017). Understanding these circuits is critical in determining how housing market shocks economic activity, societal progress and well-being (Claessens et al, 2014).…”
Section: The Conceptual Network Of Social Sustainabilitymentioning
confidence: 99%
“…We suggest starting the implementation of the model with market forces as social infrastructure outcomes which can have repercussions for societal progress and quality of life. Winkler (2017) found that the wealth effect and the financial accelerator are two aspects that connect the housing market and the broader economy. On the other hand, the sustainability orientation of executives (good housing policy) is a powerful driver for sustainable development goals.…”
Section: The Conceptual Network Of Social Sustainabilitymentioning
confidence: 99%